1996
DOI: 10.1002/(sici)1098-2396(199611)24:3<273::aid-syn10>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

In vivo SPECT imaging of 5-HT1A receptors with [123I]p-MPPI in nonhuman primates

Abstract: The in vivo imaging of a novel iodinated phenylpiperazine derivative for 5-HT1A receptors, [123I]p-MPPI (4-(2'-methoxy-)phenyl-1-[2'-(n-2"-pyridinyl)-p-iodobenzamido-] ethyl-piperazine), using single photon emission computed tomography (SPECT), was evaluated in nonhuman primates. After an i.v. injection, [123I]p-MPPI penetrated the blood-brain barrier quickly and localized in brain regions where 5-HT1A receptor density is high (hippocampus, frontal cortex, cingulate gyrus, entorhinal cortex). Maximum ratio of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 22 publications
2
17
0
Order By: Relevance
“…A similar profile was seen in the nonhuman primate brain, suggesting [ 123 I] p ‐MPPI could prove useful as a SPECT radioligand. Specific binding could be blocked by pretreatment with 8‐OH‐DPAT or WAY‐100635, as is seen both in ex vivo and in vitro autoradiographic studies . By contrast, [ 123 I] p ‐MPPI did not display specific localization to 5‐HT 1A receptor‐rich brain areas in humans.…”
Section: Current Radioligands For Imaging the 5‐ht Systemmentioning
confidence: 75%
“…A similar profile was seen in the nonhuman primate brain, suggesting [ 123 I] p ‐MPPI could prove useful as a SPECT radioligand. Specific binding could be blocked by pretreatment with 8‐OH‐DPAT or WAY‐100635, as is seen both in ex vivo and in vitro autoradiographic studies . By contrast, [ 123 I] p ‐MPPI did not display specific localization to 5‐HT 1A receptor‐rich brain areas in humans.…”
Section: Current Radioligands For Imaging the 5‐ht Systemmentioning
confidence: 75%
“…OH‐DPAT) have been discovered more than a decade ago [17], the development of selective 5‐HT 1A antagonists has been relatively slow and less successful. Recently, p ‐MPPI and p ‐MPPF have been introduced as selective antagonists for the 5‐HT 1A receptor [19–22]. These compounds bind specifically to 5‐HT 1A receptor with a high affinity.…”
Section: Resultsmentioning
confidence: 99%
“…Previously we showed that low-dose 8-OH-DPAT (1 g) produced a robust and rapid sympathoexcitatory effect in hemorrhaged rats when administered into the cisterna magna, while the same dose of drug had no effect when given systemically (34). 8-OH-DPAT readily crosses the blood-brain barrier and has significant agonist activity at 5-HT 1A and 5-HT 7 serotonergic receptors (4,19). Our earlier work also showed that the selective 5-HT 1A receptor antagonist WAY100635 dose dependently reversed the ability of centrally administered 8-OH-DPAT to maintain blood pressure during hemorrhage (35).…”
Section: Discussionmentioning
confidence: 99%